Packs, Troops and Herds: Prosocial Cooperatives and Innovation in the New Normal - Muñoz, Pablo; Kimmitt, Jonathan; Dimov, Dimo (Journal of management studies, 2020)
Prosocial organizations are emerging to tackle the effects of a New Normal. As they navigate its fragile and liquid institutional membranes, they prioritize cooperative forms of governance. These forms allow for collaboration and democratic decision‐making necessary for the development of innovative solutions in this new context. At the same time, the high coordination costs of cooperatives lead to significant market pressures. Therefore, understanding when and under what conditions these new cooperatives innovate and strive is important as it provides insight into whether and how these ventures can become a viable alternative in this changing landscape. Using configurational analyses of organizational enablers leading to innovation in 40 entrepreneurial cooperatives, we identify three approaches: Attentive Pack, Eclectic Troop, and Wandering Herd, showing that innovative outcomes can indeed emerge under traditional cooperative features emphasizing collectivism. However, the pursuit of higher novelty requires a shift to more individualistic, business‐as‐usual, approaches. The New Normal does indeed enhance entrepreneurial activity, but of a different kind comprising novel sets of antecedents and outcomes, which we show can easily become the new dominant form of venturing required in this new context.